Role of impedance drop and lesion size index (LSI) to guide catheter ablation for atrial fibrillation - Leo, M; Banerjee, A; Gala, ABE; Pope, M; Pedersen, M; Rajappan, K; Ginks, M; Bashir, Y; Hunter, RJ; Betts, T (Wiley, 2024)
Background: When using lesion size index (LSI) to guide catheter ablation, it is unclear what combination of power, contact force and time would be preferable to use and what LSI target value to aim for. This study aimed at identifying desirable ablation settings and LSI targets by using tissue impedance drop as indicator of lesion formation. Methods: Consecutive patients, undergoing their first left atrial (LA) catheter ablation for atrial fibrillation, with radiofrequency energy (RF) powers of 20, 30 and 40 W were enrolled. Tissue impedance, contact force (CF), Force Time Integral (FTI) and LSI values were continuously recorded during ablation and sampled at 100 Hz. Mean CF and Contact Force Variability (CFV) were calculated for every lesion. The effect of RF power, ablation time, CF and CFV on impedance drop and LSI were assessed. Results: A total of 3258 lesions were included in the analysis. For any target LSI value, use of higher RF powers translated into progressively higher impedance drops. The impact of lower CF and higher CFV on impedance drop was more relevant when using lower powers. Target LSI values corresponding to maximum impedance drop were identified depending on RF power, mean CF and CFV used. Conclusions: Even in the context of an LSI‐guided ablation strategy, use of lower or higher powers might lead to different lesion sizes. Different LSI targets might be needed depending on the combination of RF power, CF and CFV used for ablation. Incorporating indicators of catheter stability, like CFV, in the LSI formula could improve the predictive value of LSI for lesion size. Studies with clinical outcomes are required to confirm the clinical relevance of these findings.